THE IMPACT OF AGE-FRIENDLY ENVIRONMENTS ON THE WELLBEING OF OLDER ADULTS: EMPIRICAL EVIDENCE FROM SARAWAK - Jeffery, Stephen; Nur Azimah, Azman; Md Mizanur, Rahman; Rosalia, Saimon; Gui, Hun Chuen (IJCWED, 2026)
Despite growing evidence linking age-friendly environments (AFEs) to psychosocial wellbeing in older adults, research remains heavily skewed towards Western and urban Asian contexts. No empirical study has examined this relationship in Sarawak, a rapidly ageing, multi-ethnic state in East Malaysia with unique rural and geographic characteristics. A community-based study with 1,077 individuals aged 60 years and above in Sarawak participated in the study. Both AFEs and psychosocial wellbeing were assessed using a validated questionnaire. The domain-specific relationships were determined using robust regression analysis. Psychosocial wellness was predicted by six out of the eight AFE domains, with civic participation and employment (β=0.69) and housing (β=0.54) showing the strongest associations. Communication and information showed a significant negative association (β=−0.19), likely reflecting digital literacy challenges among elderly Sarawakians. These findings provide actionable evidence for Sarawak state planners and the Ministry of Health Malaysia to prioritise age-friendly urban and rural interventions.